2019
DOI: 10.1002/er.4486
|View full text |Cite
|
Sign up to set email alerts
|

Cauliflower‐shaped ternary nanocomposites with enhanced power and energy density for supercapacitors

Abstract: Summary The present research work aimed to study the electrochemical performance of the rGO/PPY/PANI ternary nanocomposite electrodes for supercapacitor applications. The nanocomposites have been prepared by physical blending of rGO with conducting polymers PANI and PPY in five different ratios. The prepared nanocomposites were examined by XRD, IR, Raman, SEM, and XAS characterizations, and from the results, it was found that ternary nanocomposites formed in cauliflower shape, in which PPY and PANI nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…[4][5][6][7] Generally, SCs are divided into two categories; one, referred to as electric double-layer capacitors (EDLCs), is based on the accumulation of electrolyte ions near the surface of electrode materials in the form of electrical double layer (EDL), 8,9 and the other one, referred to as pseudocapacitor, involves "reversible" Faradic reaction 10 and is mainly based on either metal oxides [11][12][13] or conductive polymers. [14][15][16][17][18] Recently, there has been great interest in pseudo-capacitors due to their relatively higher Faradic capacitances than EDLCs. 19,20 However, the long-term cycling stability and rate performance of EDLCs is superior to pseudo-capacitors, 21,22 and EDLCs are still competitive candidates for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Generally, SCs are divided into two categories; one, referred to as electric double-layer capacitors (EDLCs), is based on the accumulation of electrolyte ions near the surface of electrode materials in the form of electrical double layer (EDL), 8,9 and the other one, referred to as pseudocapacitor, involves "reversible" Faradic reaction 10 and is mainly based on either metal oxides [11][12][13] or conductive polymers. [14][15][16][17][18] Recently, there has been great interest in pseudo-capacitors due to their relatively higher Faradic capacitances than EDLCs. 19,20 However, the long-term cycling stability and rate performance of EDLCs is superior to pseudo-capacitors, 21,22 and EDLCs are still competitive candidates for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…All the specific capacitance values for two and three electrode systems have been given in Table 1. 45 Zhaofen et al has reported a specific capacitance of 160.5 F/g for aniline-grafting graphene oxide/PANI (GO-ANI/PANI) composite. 45 Zhaofen et al has reported a specific capacitance of 160.5 F/g for aniline-grafting graphene oxide/PANI (GO-ANI/PANI) composite.…”
Section: Figurementioning
confidence: 99%
“…Supercapacitors (SCs) were regarded as one of the most promising energy storage devices because of their superior power density, fast charge/discharge process, and ultralong cycle stability . But the practical applications of SCs were dramatically limited by the low energy density . Currently, battery‐supercapacitor hybrid (BSH) device composed of a capacitive electrode and a battery‐type electrode was used to increase energy density .…”
Section: Introductionmentioning
confidence: 99%